Navigating herpes simplex encephalitis: Family medicine perspectives from Jharkhand, India - Amit Kumar Patel; Ashok Kumar Sharma; Kumari Seema; Abhay Kumar; Manju Boipai; Rishi Tuhin Guria; Upendra Prasad Sahu; Manoj Kumar (Journal of Family Medicine and Primary Care)
Background: Herpes simplex encephalitis (HSE), caused by herpes simplex virus (HSV) is the most common cause of sporadic encephalitis that often presents as an emergency case of acute or sub-acute nature associated with poor prognosis. Early suspicion and prompt diagnostic testing with adequate antiviral therapy can only reduce morbidity and mortality associated with the disease. This study aims to evaluate the role of serological and molecular diagnosis of encephalitis caused by HSV 1 and 2 for timely detection of the disease. Methods: This cross-sectional study was conducted at the Department of Microbiology, Rajendra Institute of Medical Science, Ranchi, from April 2021 to September 2022. Cerebrospinal fluid (CSF) samples were collected and processed for the detection of HSV DNA by polymerase chain reaction (PCR) as well as serum samples were collected from those patients and were processed for the detection of IgM by ELISA. Results: A total of 188 CSF samples were collected, out of which 4 HSV-1 and 1 HSV-2 samples were found to be positive by conventional PCR. 36 samples were positive for HSV-1 and 2 IgM ELISA. 26.06% of cases belonged to patients between 0 and 10 years of age followed by 17.06% in 51-60 years age groups. Conclusion: PCR is the optimal diagnostic test, but the sample must be collected in the early stages of the disease. Diagnosis by PCR assay of CSF samples targeting HSV DNA is the best confirmatory test at hand for early detection and also helps in estimating the incidence of herpes simplex virus encephalitis.